2006
DOI: 10.1207/s15328023top3302_1
|View full text |Cite
|
Sign up to set email alerts
|

The Teacher Behaviors Checklist: Factor Analysis of Its Utility for Evaluating Teaching

Abstract: We converted the Teacher Behaviors Checklist (TBC;Buskist, Sikorski, Buckley, & Saville, 2002) to an evaluative instrument to assess teaching by adding specific instructions and a Likert-type scale. Factor analysis of the modified TBC produced 2 subscales: caring and supportive and professional competency and communication skills. Further psychometric analysis suggested the instrument possessed excellent construct validity and reliability, underscoring its potential as a tool for assessing teaching. This instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
204
0
18

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(243 citation statements)
references
References 9 publications
19
204
0
18
Order By: Relevance
“…Additional course content may provide an opportunity for students to assess their degree of possible rapport with the instructor through perceived instructor enthusiasm about the material. These two impressions are consistent with two aspects of teaching effectiveness, found in past research (Keeley, Smith, and Buskist 2006). As such, the first aim of this study seeks to examine the effects of detail type on instructor effectiveness perceptions.…”
Section: Course Syllabi and Instructor Perceptionssupporting
confidence: 82%
“…Additional course content may provide an opportunity for students to assess their degree of possible rapport with the instructor through perceived instructor enthusiasm about the material. These two impressions are consistent with two aspects of teaching effectiveness, found in past research (Keeley, Smith, and Buskist 2006). As such, the first aim of this study seeks to examine the effects of detail type on instructor effectiveness perceptions.…”
Section: Course Syllabi and Instructor Perceptionssupporting
confidence: 82%
“…An alternative explanation to our findings may be that teachers who are invested in empirically testing their teaching innovations possess other qualities such as rapport (e.g., Benson, Cohen, & Buskist, 2005;Buskist, Sikorski, Buckley, & Saville, 2002;Keeley, Smith, & Buskist, 2006;Schaeffer, Epting, Zinn, & Buskist, 2003), immediacy skills (e.g., Mehrabian, 1969;Wilson & Taylor, 2001), or a working alliance with students (Meyers, 2008) that also may influence learning outcomes. For example, it may be that these teachers also possess important relationship qualities or skills that contribute to the effectiveness of their activities.…”
Section: Discussionmentioning
confidence: 84%
“…Smyth et al (2012) stated clear expectation of assessment and prompt feedback are important factors for enhancing student experience. Arambewela and Hall (2009), Keeley et al (2006) and Roger and Smith (2011) also discussed the importance of staff enthusiasm in the creating of a supportive learning environment, which is considered within Factor 2 (F2) of the current study. Factors 1, 2, 4 and 5 identified in this paper supported the findings of previous literature.…”
Section: Factor Analysismentioning
confidence: 98%
“…Rogers and Smith (2011) identified the best joint predictors of overall satisfaction as the academics' genuine interest in the individual's learning needs and progress, development of understanding of concepts and principles, and clear expectation of the course. Arambewela and Hall (2009) and Keeley et al (2006) suggested that a staff's genuine interest in a student's work is shown by having an encouraging and supportive attitude, praising good work and providing additional assistance to students who need it. Ramsden's (1991) research cited several studies that acknowledged the importance of empathy.…”
Section: Dimension and Measurement Of Student Satisfactionmentioning
confidence: 99%